Prognostic value of baseline 18F‐FDG PET/CT metabolic parameters in paediatric lymphoma. Issue 1 (27th December 2019) - Zhou, Yeye; Hong, Zhihui; Zhou, Min; Sang, Shibiao; Zhang, Bin; Li, Jihui; Li, Qingru; Wu, Yiwei; Deng, Shengming
Abstract: Introduction: In the present study, we aimed to investigate the prognostic value of metabolic parameters, including maximum standardized uptake value (SUVmax ), total metabolic tumour volume (tMTV) and total lesion glycolysis (TLG), measured at baseline 18 F‐FDG PET/CT in paediatric lymphoma. Methods: From March 2013 to April 2019, 47 patients with paediatric lymphoma, including 38 males and nine females with an average age of 14.87 years, who underwent 18 F‐FDG PET/CT scan prior to treatment were retrospectively included in this study. SUVmax, MTV and TLG were recorded. Survival curves were established according to the Kaplan–Meier curves and log‐rank test. Mann–Whitney U ‐test was used to assess differences in metabolic parameters between different clinical outcomes. Results: The median follow‐up time was 36 months (range of 3–74 months). The 2‐year progression‐free survival (PFS) of the low TLG and high TLG groups was 95.24% (20/21) and 57.69% (15/26), respectively ( P  = 0.004). TLG and tMTV were significantly higher in progression‐free patients compared with the progression group. Univariate analysis showed that B symptoms ( P  = 0.014), effusion ( P  = 0.010), tMTV ( P  = 0.008) and TLG ( P  = 0.004) were the predictive factors for PFS. The tMTV ( P  = 0.005), TLG ( P  = 0.005) and effusion ( P  = 0.003) were associated with OS. Multivariate analysis revealed that TLG was the only independent prognostic factor for PFS (HR = 11.133, 95% CI = 1.435–86.405, P  = 0.021). Conclusions: Collectively, TLG of baseline 18 F‐FDG PET/CT was an independent prognostic factor for PFS in patients with paediatric lymphoma.